Posyandu and Posbindu Development - Widawati, Widawati; Sihombing, Kristin; Angelina, Ria; Hariningsih, Wintari; Tambunan, Rosalina; Sitorus, Netti; Ardayani, Tri; Sariningsih, OD (Aktual: Jurnal Pengabdian Kepada Masyarakat, 2023)
This service program aims to nurture health cadres in managing and running posyandu and posbindu. Community service methods are carried out by counseling, lectures, questions and answers, pre-test and post-test. The media used are televisions and laptops to display material in the form of power points. The stages of implementation carried out in this service are conducting a pre-test, then providing material and continued with a post test. The results of this community service activity have answered the problem of strengthening health cadres in managing, running posyandu and posbindu. This activity has been considered beneficial for cadres, although it has not been felt by many elderly and toddlers. This can be seen from the comparison of pre-test and post-test results which show an increase in cadre knowledge. Community service activities can then be continued with research first to find out the problems that exist in the community.